PROGNOSIS AND OUTCOME OF PATIENTS ADMITTED IN ICU DIAGNOSED TO HAVE RESPIRATORY FAILURE (Indian Journal of Applied-Basic Medical Sciences, 2020)
Prognosis and outcome of patients admitted in ICU, diagnosed to have respiratory failure. Introduction: Acute respiratory failure is one of the most common reasons for ICU admission. In some ICUs, >75% of patients require mechanical ventilation during their stay. It is useful to identify patients at the time of admission who are likely to have poor outcome. This study was carried out to evaluate efficacy of the predictors of mortality in patients with acute respiratory failure and use this scoring system using the baseline physiological variables for prognosticating these patients. Material and method: A prospective observational study was conducted in Dept of internal medicine at tertiary care hospital in Ahmedabad for a period of 6 months. Patients having breathlessness requiring Intensive care were observed and 100 patients having respiratory failure were enrolled in study. Clinical profile including APACHE II score and Glasgow coma scale was recorded at the time of admission to ICU. In addition, acid base disorders, renal functions, liver functions and serum albumin were recorded at the time of presentation. Primary outcome measure was hospital mortality. Results were assessed using chi square test.Results: In our study we found male predominance. Majority patients were in the age group 60-70 years. Among the study group, cause of respiratory failure were Acute COPD exacerbation (37%) followed by LRTI (26%), Cardiac (22%), Bronchiectasis (7%), ARDS/ Sepsis (5%) and Pneumothorax (3%) in decreasing order. Majority of the patient who had high APACHE 2 score on first day of their stay in ICU, had high mortality Conclusion: APACHE 2 score is a good predictor of patient’s mortality. Using this routinely can help to prioritize the patients especially in resource limited setups. Hence better outcomes can be achieved.
Keywords: Acute respiratory failure; APACHE 2 Score